Transcriptional heterogeneity in the lactase gene within cell-type is linked to the epigenome - Oh, Edward; Jeremian, Richie; Oh, Gabriel; Groot, Daniel; Susic, Miki; Lee, KwangHo; Foy, Kelly; Laird, Peter W.; Petronis, Arturas; Labrie, Viviane (Scientific reports, 2017)
Transcriptional variation in histologically- and genetically- identical cells is a widespread phenomenon in tissues, yet the processes conferring this heterogeneity are not well understood. To identify contributing factors, we analyzed epigenetic profiles associated with the in vivo transcriptional gradient of the mouse lactase gene ( Lct ), which occurs in enterocytes along the proximal-to-distal axis of the small intestine. We found that epigenetic signatures at enhancer and promoter elements aligns with transcriptional variation of Lct in enterocytes. Age and phenotype-specific environmental cues (lactose exposure after weaning) induced changes to epigenetic modifications and CTCF binding at select regulatory elements, which corresponded to the alterations in the intestinal Lct mRNA gradient. Thus, epigenetic modifications in combination with CTCF binding at regulatory elements account for the transcriptional gradient in Lct in cells of the same type. Epigenetic divergence within enterocytes may contribute to the functional specialization of intestinal subregions.